PENGEMBANGAN LKS SMA PADA MATERI BIOTEKNOLOGI KONVENSIONAL MELALUI EKSPERIMEN PEMBUATAN TEMPE MENGGUNAKAN BERBAGAI JENIS KACANG - Kharisma, Hesti Kharisma; Mahadi, Imam Mahadi; ', Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Tempeh is alimentary one be resulted through simple ferment tech by Rhizopus sp . All this time tempeh what do be at marketing just that gets soybean raw product. While many moke production the last years at Indonesian continually decreases and can't meet the need. Therefore, need developed tempeh's makings that utilize materials any other that appreciative its nutrient doesn't succumb good with tempeh of moke as adzuki bean, mung bean and peanut. To the effect of observational it is subject to be know good bean type deep tempeh's makings and this research result gets to be utilized for LKS SMA'S development Bioteknologi Conventional material. This research comprise of 2 phases, which is first phase, tempeh's makings whereas phase both of, LKS'S development of research result. tempeh's makings research this utilize experiment research with RAL that consisting of 4 conducts and 3 dry runs. Observational result to be gotten that conclusion is sighted from water rate content, ash rate, protein rate and fat rate and organoleptik, soybean and adzuki bean is good bean deep tempe's makings. Soybean has to titrate water 54,30%, ash rate 0,21%, protein rate 17,57% and fat rate 0,72%. Meanwhile adzuki bean has to titrate water 60,23%, ash rate 0,31%, protein rate 17,85% and fat rate 0,62%. Observational result can be developed as LKS SMA Bioteknologi Conventional material. Key word: tempeh, a variety bean type, conventional bioteknologi, LKS